2017
DOI: 10.1002/gcc.22450
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16A/ANO1 suppression improves response to antibody‐mediated targeted therapy of EGFR and HER2/ERBB2

Abstract: TMEM16A, a Ca2+-activated Cl− channel, contributes to tumor growth in breast cancer and head and neck squamous cell carcinoma (HNSCC). Here, we investigated whether TMEM16A influences the response to EGFR/HER family-targeting biological therapies. Inhibition of TMEM16A Cl− channel activity in breast cancer cells with HER2 amplification induced a loss of viability. Cells resistant to trastuzumab, a monoclonal antibody targeting HER2, showed an increase in TMEM16A expression and heightened sensitivity to Cl− cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…1F). These results are in agreement with previous studies demonstrating the association of TMEM16A expression with the EGFR signaling pathway in breast cancer and HNSCC (11,12,22). Given that the EGFR signaling pathway in pancreatic cancer relies on the EGFR ligands (13,14) and promotes pancreatic ductal adenocarcinoma (PDAC) development by regulating acinar-ductal metaplasia, cancer cell migration, and the occurrence of metastasis (15,17,18,23), our finding suggests that TMEM16A could play an essential role in ligand-induced EGFR signaling pathway in pancreatic cancer.…”
Section: Tmem16a Is Overexpressed In Pancreatic Ductal Adenocarcinomasupporting
confidence: 92%
“…1F). These results are in agreement with previous studies demonstrating the association of TMEM16A expression with the EGFR signaling pathway in breast cancer and HNSCC (11,12,22). Given that the EGFR signaling pathway in pancreatic cancer relies on the EGFR ligands (13,14) and promotes pancreatic ductal adenocarcinoma (PDAC) development by regulating acinar-ductal metaplasia, cancer cell migration, and the occurrence of metastasis (15,17,18,23), our finding suggests that TMEM16A could play an essential role in ligand-induced EGFR signaling pathway in pancreatic cancer.…”
Section: Tmem16a Is Overexpressed In Pancreatic Ductal Adenocarcinomasupporting
confidence: 92%
“…Furthermore, recent data using the RIP-kinase inhibitor, necrostatin, suggest that TMEM16A knockdown induced cell death does not proceed in a necroptotic manner [19]. While this does not preclude the involvement of other cell death pathways (e.g., autophagy), it does suggest that apoptotic cell death is a key mediator.…”
Section: Discussionmentioning
confidence: 98%
“…These results suggest that ClC‐3 inhibitor might promote trastuzumab resistance through activation of the PI3K/AKT/mTOR signaling pathway. Kulkarni et al recently reported that ANO1 contributed to the acquirement of resistance to anti‐HER2 therapies. However, our main finding is that ANO1/ClC‐3 inhibition downregulates the expression levels of HER2 proteins through transcriptional repression of it, suggesting that targeting ANO1/ClC‐3 may prevent resistance to anti‐HER2 therapies in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the present results indicate the importance of ANO1/ClC‐3 in therapeutics for HER2‐positive breast cancer with resistance to anti‐HER2 therapies. ANO1 expression has been investigated in cancer patients categorized according to estrogen receptor, progesterone receptor, and HER2, and a recent report showed that breast cancer cells resistant to trastuzumab showed upregulation of ANO1 . Correlation between chemotherapy drug resistance and ClC‐3 expression is well known; however, ClC‐3 expression in categorized cancer patients has not been sufficiently studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation